Book Review: Heritage at War - David Malcolm Dean (Museum & Society)
Book review of Mark Dunkley, Lisa Mol, and Anna Tulliach (eds), Heritage at War: Plan and Prepare, Winwick, Cambridgeshire: The White Horse Press, 2024, hardback £65.00, pp. xx+213